The United Nations Convention on the Use of Electronic Communications in International Contracts at Ten: Practical Relevance and Lessons Learned - Castellani, Luca G. (Journal of Law, Society and Development, 2016)
The United Nations Commission on International Trade Law prepared the first global treaty specifically devoted to electronic commerce law, the United Nations Convention on the Use of Electronic Communications in International Contracts. That treaty builds on the highly successful UNCITRAL Model Law on Electronic Commerce and the UNCITRAL Model Law on Electronic Signatures. This article describes the main goals of the Electronic Communications Convention and its scope of application. In particular, it illustrates how that Convention may fully enable the use of electronic means under other widely adopted treaties such as the Convention on the Recognition and Enforcement of Foreign Arbitral Awards and the United Nations Convention on Contracts for the International Sale of Goods. The article also describes the main substantive provisions of the Electronic Communications Convention, in particular clarifying how that Convention updates and completes the provisions of the UNCITRAL Model Law on Electronic Commerce. This Model Law is the backbone of electronic commerce law in numerous countries and a de facto legislative standard insouthern Africa. Finally, the article describes the manner (or patterns) in which the adoption of the Electronic Communications Convention takes place. It stresses that, while the Convention is often used as a source of inspiration for domestic law reform, in order for it to achieve all its intended goals, its formal adoption as a treaty is necessary. The final message is therefore a call upon all states to consider the adoption of that Convention in order to support the broader use of electronic means, especially in the light of the implications for economic development and the promotion of paperless trade.
Keywords: Convention adoption patterns; Digital signatures; Electronic communications; Electronic contracting; Legal harmonisation

Regional Harmonisation of Contract Law - Is It Feasible? - Zeller, Bruno (Journal of Law, Society and Development, 2016)
This article investigates whether regional harmonisation is merely an academic exercise or a serious attempt to create a uniform contract law in a defined region. It builds on the recently conducted Symposium at Villanova University in 2013 and addresses comparatively the efforts by well-defined regions, namely OHADA, the EU and ASEAN. OHADA has introduced regional uniform laws; the EU is still working on formulating them. Furthermore, UNCITRAL has considered a proposal by the Swiss government to work urgently on a new initiative to further harmonise contract law. Against this backdrop, this article argues that regional proposals to harmonise contract law are akin to saying that ‘ein Gespenst geht um’ (a ghost is going around) (Reich 2006: 425). This is justified, because a proposal to create a harmonised contract law in East Asia has currently also been discussed, but the discussions have stalled. Is there a solution or do we simply admit that regional harmonisation is not possible? The starting point is the CISG, as has been adopted by 80 countries and needs to be considered by any region as a possible, albeit not perfect, solution. If the CISG has already been ratified, the issue, then, is how any regional developments can coexist with it. Or does a ratification of the CISG preclude any regional harmonisation? Secondly, the question must be asked whether regional harmonisation will reduce transaction costs, which is beyond what the CISG was able to achieve. This article argues that as far as the drafting of international instruments isconcerned, a shift in thinking has occurred. Instruments such as the Cape Town Convention are considered to be reforming the law in a particular narrow area rather than attempting to draft codes. Furthermore, the process is driven by industry groups. Regional harmonisation must take note of the ongoing shift and a more fruitful approach is to develop uniform laws through a better understanding and coordination of existing instruments.
Keywords: CISG; Contract law; Regional harmonisation; Uniform law

Dealing with trade defence instruments in the context of economic integration in Africa - El Taweel, Khaled (University of Pretoria, 2016)
The launching of the T-FTA in June 2015 presents an opportunity for accelerating regional integration in Africa towards the establishment of a single market through deepening COMESA-EAC-SADC integration. This milestone can contribute positively to African development. Nevertheless, it faces different structural and technical challenges, including the risk of aggressive export strategies and unfair trade practices, which may wipe away a substantial part of the integration gains. This could undermine African integration plans and the largely infant industries in Africa, especially since many African countries lack sufficient technical skills, institutional capacity, and the legal framework to deal efficiently and effectively with unfair trade practices and to respond to situations which may require the application of emergency tools to better adapt to economic challenges. Apart from Egypt, Morocco, Tunisia, South Africa and Zambia national Trade Defence Instruments (TDIs) are not well developed. This could further constrain the ambitious African plans of economic integration. The thesis concludes that, although an effective TDI system is crucial for African integration as it can provide the required protection for African infant industries and unlock the potentials of African economic integration, the current African TDI systems are not effective. This is confirmed by the limited resort to TDIs in the African continent and the general perception that an effective TDI system is not a priority on the integration agenda. The concluded T-FTA TDI legal regime is not supportive for African integration plans in the long run. Africa should envisage how to upgrade its TDI system to make better use of the tools available under the WTO to deal with unfair trade measures, including anti-dumping to face dumped imports, countervailing measures to face subsidized imports, and safeguard measures to temporarily suspend concessions in the face of surge in imports. Africa can improve its national and regional TDIs system by learning from more developed TDI systems incorporated by other economic blocks such as the EU, NAFTA, Mercosur, and ASEAN. This thesis submits that the EU TDIs system is the most suitable to the African integration objectives. This submission is made while recognising the different level of development on both sides. The thesis submits that the long-term objective of the T-FTA is to have a regional investigating authority. It draws several recommendations to enhance African TDI system by working on five main categories: (A) The strategic direction; (B) The institutional framework; (C) Enhancing engagements; (D) Application of TDIs; and (E) The supportive factors.
URI: https://repository.up.ac.za/handle/2263/60043
Keywords: Economic integration; Trade defence instruments; Unfair trade practices

Private Ordering of Exit in Limited Liability Companies: Theory and Evidence from Business Organization Contracts - Gomtsian, Suren (American Business Law Journal, 2016)
https://onlinelibrary.wiley.com/doi/10.1111/ablj.12087

Contracts Governing the Use of Websites - Mik, Eliza (Singapore Journal of Legal Studies, 2016)
With the progressive transformation of the Internet from a romanticised instrument of freedom and self-expression into a commercial platform for digital distribution, most websites must be recognised as access interfaces to a wide range of content and services. This paper examines the contracts purportedly governing the use of such content and services. It explores the difficulties of establishing legal intention in a context that is not unambiguously commercial or transactional and contrasts popular beliefs with the basic principles of contract law. It draws a clear distinction between contracts governing traditional e-commerce exchanges, such as buying books on Amazon.com, and contracts governing the very use of websites. In the latter instance, the website (ie the resources made available thereon) constitutes the subject matter of the transaction. Equal importance must be attributed to the fact that such contracts are formed on websites and to the fact that they govern their use. The website user will question the existence of a contract on the basis that he did not have an intention to be legally bound, or had no awareness that a transaction was taking place. The website operator will argue that, objectively, all prerequisites of a legally enforceable agreement have been met. The outcome of the discussion will, to a large extent, depend on whether the user’s beliefs and expectations can be regarded as reasonable and on whether it is the user or the operator who deserves the protection of the objective theory of contract.